Moderating Effect Of Firm Size On The Influence Of Profitability On Asean Stock Returns - Komara, Esi Fitriani; Waspada, Ikaputera; Disman, Disman; Supriatna, Nono (Indonesian Journal of Sustainability Accounting and Management, 2025)
Profitability is a factor that can affect the amount of stock returns. Therefore, it is important to recognize the elements that can enhance or lessen the influence of profitability on stock returns. The effect of conditions that are thought to strengthen or weaken is the size of the Company. Therefore, the aim of this research is to analyze how company size moderates the effect of profitability on ASEAN stock returns between 2014 and 2023. The data analysis used is moderated regression analysis process Macro hayes using the feature programme in SPSS, with a total sample of 6,130 companies from 5 ASEAN countries during the period 2014–2023. The source material analyzed consists of secondary data. The study showed that company size plays a role in mitigating the effect of profitability on stock returns of ASEAN countries for the period 2014–2023.